Political connections, media monitoring and long-term loans - Deming Yang; Zhengfei Lu; Danglun Luo (China Journal of Accounting Research, 2014)
We analyze data on Chinese non-state-listed firms and find that it is easier for firms with political connections to obtain long-term loans with extended debt maturities than it is for firms without political connections. Our investigation indicates that this phenomenon is significantly less common with increased media monitoring. Houston et al. (2011) find strong evidence that the state ownership of media is associated with higher levels of bank corruption in China, but our study shows that, to a certain extent, media monitoring can curb corruption.
Keywords: G34; D21; L51; 650; Political connections; Long-term loans; Media monitoring